Toxic chemicals in the workplace - Fraser, T. M. (Thomas Morris), 1922- (Gulf Pub., 1996)
This book examines toxic chemicals that may be present in the workplace and--with easy-to-understand, nontechnical language--examines the steps an organization can take to manage them.